Left Ventricular Hypertrophy dan Fungsi Ginjal pada Penderita Hipertensi - HERU SULASTOMO; FADLAN AKHYAR FAUZI; RATNA KUSUMAWATI (Smart Medical Journal, 2018)
Introduction: Chronic hypertension can cause complication such as left ventricular hypertrophy (LVH).  LVH can lead renal artery vasoconstriction, impaire blood perfusion to glomerulus and change glomerulus filtration coeficient. The aim of this study was tocompare kidney function between hypertensive patient with LVH and without LVHMethods: This was a case control study that conducted at Dr. Moewardi GeneralHospital Surakarta. All subjects has been diagnosed as hypertension more than 5 years.The diagnosis of LVH was based on electrocardiography (ECG) result. Kidney functionwas assessed based on serum ureum, creatinin, and uric acid  levels.Results: The subject of this study was 26 hypertension patients with LVH and 13hypertension patients without LVH. Serum ureum level in patients with LVH was higherthan hypertension patients without LVH(24.92 ± 7.99 Vs 32.33±9.91, p= 0.004). Serumuric acid level in hypertension patients with LVH was higher compare to hypertensionpatients without LVH as well (5.26 ± 1.15 Vs 6.98 ± 1.83, p= 0.029). Whereas serumcreatinine levels were not significantly different between two groups of subjects.  Sulastomo et.al., Left Ventricular Hypertrophy dan Fungsi Ginjal pada Penderita Hipertensi Conclusion: : Serum ureum and uric acid levels in hypertensive subjects with LVH arehigher than subjects without LVH. There is no difference between serum creatinin level inhypertensive subject with LVH and without LVH.